Challenges of Allied Healthcare Professionals in India–Establishing the Council is Need of the Hour - Alka Rawekar1 , Shashank Gotarkar2 , Swapnil Patond3 , Sarika Dakhode2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
There is a supply-demand gap of about 65 lakh allied health professionals in India. With India facing aheavy burden of disease with many challenges as achieving millennium development goals, shortage ofskilled manpower will be a great hurdle for the health care delivery system. In such a situation, AlliedHealth workers can play a major role in providing holistic health services to the community. Though manyinstitutions or Universities in India are generating allied healthcare professionals, there is no uniformityin the outcome of such professionals. There is no standardization of this professional till date. Hence, toestablish a Centralized council is a need of an hour so that all such programs will come under a commonplatform and generated manpower will be able to provide the necessary services to the community. Inthis article, some suggestions are provided to improve the quality of AHPs, like estimation of workforceaccording to WHO requirement, uniformity in curricula, common nomenclature for all programs, creatingjob opportunities in private and public sectors etc.